Near-grain-boundary characterization by atomic force microscopy - Pramanick A.K.; Sinha A.; Sastry G.V.S.; Ghosh R.N. (My University, 2025)
Characterization of near-grain boundary is carried out by atomic force microscopy (AFM). It has been observed to be the most suitable technique owing to its capability to investigate the surface at high resolution. Commercial purity-grade nickel processed under different conditions, viz., (i) cold-rolled and annealed and (ii) thermally etched condition without cold rolling, is considered in the present study. AFM crystallographic data match well with the standard data. Hence, it establishes two grain-boundary relations viz., plane matching and coincidence site lattice (CSL Σ=9) relation for the two different sample conditions. © 2009 Elsevier B.V. All rights reserved.